2008
DOI: 10.1177/0269881108093588
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for schizophrenia patients with clozapine treatment: how good does it get?

Abstract: The objective of this study was to describe the extent/change (2000-2004) of clozapine prescribing in schizophrenia in New Zealand and examine the outcomes associated with increasing treatment duration, and vs. those who discontinue clozapine. Consecutive chart reviews were conducted for adult outpatients in Auckland/Northland regions (T1 = 31 March 2000, T2 = 31 October 2001, T3 = 31 March 2003, T4 = 31 October 2004). Data collected included: patient characteristics, social/functional indicators, diagnosis, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
1
44
0
1
Order By: Relevance
“…Clozapine induced cardiomyopathy does not appear to be dose dependent [9]. In this review, the range of doses for patients with reported cardiomyopathy was 125 mg-700 mg, with a mean dose of 360 mg.…”
Section: Dosingmentioning
confidence: 75%
See 1 more Smart Citation
“…Clozapine induced cardiomyopathy does not appear to be dose dependent [9]. In this review, the range of doses for patients with reported cardiomyopathy was 125 mg-700 mg, with a mean dose of 360 mg.…”
Section: Dosingmentioning
confidence: 75%
“…Clozapine also has been shown to reduce aggression more effectively than other antipsychotics; in patients with a history of violence it allows them to reengage safely with society and family after forensic and prison settings [8]. There is strong evidence that patients with schizophrenia on clozapine -despite being classified as treatment-resistant -are significantly more likely to live independently and to be employed when compared to other medications [9]. Finally, in a recent study of 66,681 patients followed over 11-years, patients on clozapine were shown to have the lowest overall mortality and fewest deaths due to ischemic heart disease as compared to the eight most commonly used typical and atypical antipsychotic agents [10].…”
Section: Introductionmentioning
confidence: 99%
“…34 Similarly, patients meeting criteria for TRS frequently demonstrate a favourable response to clozapine, but this is not necessarily matched by improvements in functional measures. 22,35 Longer-term, follow-up studies have also demonstrated that clinical and functional recovery do not parallel each other across time. 23 More recently, it has been argued that other symptom domains may play a more critical role in functional outcome.…”
Section: Removal Of Functioning In Evaluating Treatment Responsementioning
confidence: 99%
“…[1][2][3] Schizophrenia is a devastating condition for those that are afflicted as well as their families and friends. Further schizophrenia, also exacts a tremendous toll upon society, economically through service utilization, and lost productivity.…”
Section: Introductionmentioning
confidence: 99%